Web STIM (Flash Memory Simulator) / Nurul Ain Maizan - Nurul Ain , Maizan (2005)
Web STIM is a Web-sensor by means of interior data structure and communication functionalities and a smart sensor able to interface its If with Internet through an Ethernet network. Web STIM is designed to satisfy requirements of low cost, continuous acquisition and data processing, and wide remote communication capability as describe in the IEEE 1451 standard. It is use HTTP interface that replace the T11 (Transducer Independent Interface) hardware, which has been inspired by IEEE 1451.2 standard. This paper describe the Transducers Electronic Datasheet (TEDS) directly interfaced to internet through an HTTP based procedure. Web STIM is a web based system that can be access directly directly through internet connection by diffuse software on the world.